ZIARAH DAN PENDIDIKAN MORAL: (STUDI TENTANG PROFESIONALISME GURU DALAM PEMBENTUKAN KARAKTER KEISLAMAN DI KALANGAN SISWA MADRASAH) - Munawwir, Munawwir; Rosyidah, Lu’luatur; Nahdhiyyah, Zumrotun (TA’LIM : Jurnal Studi Pendidikan Islam, 2025)
<!–StartFragment–> Ziarah (pilgrimage) is an Islamic tradition with both spiritual and educational values, making it a potential tool for character development in madrasah students. This study aims to analyze the concept of ziarah in Islam and education, the relationship between moral education and Islamic character formation, and the professionalism of teachers in shaping students’ character. Additionally, this research explores the relevance of ziarah to moral education in madrasah and the role of teachers in fostering Islamic character through pilgrimage activities. This study employs a qualitative descriptive approach using literature analysis and observation techniques. The findings indicate that ziarah has significant potential in strengthening moral education in madrasah, particularly in fostering religious, social, and ethical values in students. As professional educators, teachers play a crucial role in guiding the meaning and experience of ziarah so that it is not merely a religious routine but also an effective means of shaping a strong Islamic character. With proper guidance, ziarah can serve as an effective moral education strategy in madrasah settings. <!–EndFragment–>